Radiation dose-response model for locally advanced rectal cancer after pre-operative chemoradiotherapy - Appelt, Ane L. (2012)
PURPOSE: Preoperative chemoradiotherapy (CRT) is part of the standard treatment of locally advanced rectal cancers. Tumour regression at the time of operation is desirable, but not much is known about the relationship between radiation dose and tumour regression. In the present study we estimated radiation dose-response curves for various grades of tumour regression after preoperative CRT. METHODS AND MATERIALS: A total of 222 patients, treated with consistent chemotherapy and radiotherapy techniques, were considered for the analysis. Radiotherapy consisted of a combination of external beam radiotherapy and brachytherapy. Response at the time of operation was evaluated from the histopathological specimen and graded on a five point scale (TRG1-5). The probability of achieving complete, major and partial response was analyzed using ordinal logistic regression, and the effect of including clinical parameters in the model was examined. The radiation dose response relationship for a specific grade of histopathological tumour regression was parameterized in terms of the dose required for 50% response, D(50,i), and the normalized dose-response gradient, γ(50,i). RESULTS: A highly significant dose–response relationship was found (p=0.002). For complete response (TRG1) the dose-response parameters were D(50,TRG1)=92.0 Gy (95% CI: 79.3 to 144.9 Gy), γ(50,TRG1)=0.982 (0.533 to 1.429), and for major response (TRG1-2) D(50,TRG1&2)=72.1 Gy (65.3 to 94.0 Gy), γ(50,TRG1&2)=0.770 (0.338 to 1.201). Tumour size and N-category both had a significant effect on the dose-response relationships. CONCLUSIONS: This study has demonstrated a significant dose-response relationship for tumour regression after preoperative CRT for locally advanced rectal cancer for tumour dose levels in the range of 50.4 to 70 Gy, which is higher than the dose-range usually considered.